Is There a Role for Agomelatine in the Treatment of Anxiety Disorders? A Review of Published Data. (April 2013) - De Berardis, D.; Conti, C.M.; Marini, S.; Ferri, F.; Iasevoli, F.; Valchera, A.; Fornaro, M.; Cavuto, M.; Srinivasan, V.; Perna, G.; Carano, A.; Piersanti, M.; et al.
Anxiety disorders (ADs) are the most common type of psychiatric disorders. Pharmacologic options studied for treating ADs may include benzodiazepines, tricyclic antidepressants (TCA), selective serotonin reuptake inhibitors (SSRIs), noradrenergic and specific serotonergic antidepressants (NaSSA) and serotonin and noradrenaline reuptake inhibitors (SNRIs). Agomelatine, a new melatonergic antidepressant, has been shown effective in various types of mood disorders. Moreover, some evidence points towards a possible efficacy of such a drug in the treatment of ADs. Therefore, the aim of this review was to elucidate current (facts and views) data on the role of agomelatine in the treatment of ADs. The trials evaluating agomelatine in the treatment of generalized anxiety disorder are few but, overall, encouraging in regards to its efficacy. However, further randomized, placebo-controlled studies on larger samples use are needed. Apart from some interesting case reports, no large studies are, to date, present in literature regarding agomelatine in the treatment of other ADs, such as panic disorder, social anxiety disorder, obsessive-compulsive disorder and post-traumatic stress disorder. Therefore, the clinical efficacy and the relative good tolerability of agomelatine in generalized anxiety (GAD) warrants further investigation in ADs.